Neuroprotective effects of a novel peptide through the Rho-integrin-Tie2 and PI3K/Akt pathways in experimental autoimmune encephalomyelitis model - Zhou, Wen; Qu, Han; Fu, Xiao-Xiao; Xu, Miao-Miao; Li, Qiang; Jiang, Yuan; Han, Shu (Frontiers in Pharmacology, 2024)
Purpose: The interaction between inflammatory cells and integrin in the endothelium plays a key role during infiltration. Previous evidence has shown that synthetic C16 peptide selectively binds to integrins αvβ3 and α5β1 and exhibits a neuroprotective effect. It has also been reported to inhibit the differentiation of microglia into the M1 (pro-inflammatory) phenotype while promoting its differentiation to the M2 (anti-inflammatory) phenotype. This study aimed to investigate the mechanisms of action of the C16 peptide in multiple sclerosis using a rodent model. Methods: Molecular, morphological, and neurophysiological assays were used to investigate the neuroprotective effects of C16 peptide and related signaling pathways in a model of EAE. Results: The results showed that C16 significantly improved the clinical score and cortical somatosensory/motor evoked potential. It also alleviated inflammatory responses, including microglial activation and leukocyte infiltration, relieved the impairment of the brain blood barrier and edema, and reduced neuronal apoptosis, axonal loss, and demyelination induced by EAE. The C16 peptide increased the expressions of pTie and Tie-2, integrin αvβ3, and α5β1 and activated the PI3K/Akt signal pathway but decreased the expression of Rho. Co-treatment of C16 with Tie-2 inhibitor and PI3K inhibitor LY294002 attenuated these effects of C16. Conclusion: The C16 peptide demonstrated neuroprotection in the EAE model through the integrin, Tie-2, and PI3K/Akt signaling pathways, and it could be a potential strategy for treating inflammation-related diseases in the central nervous system.